The four gates of the African markets - (:unkn) unknown (My University, 2012)
Africa, which had only 230 million consumers in 1950, became a billionaire population in the late 2000s. In addition, the continent could experience the highest population growth, bringing its population to 1446 million in 2025 and 2339 million in 2050 if the average projection is realized, so if the economic and health conditions allow this increase. Four questions are addressed: What countries do you account the most current consumers and future? In which countries consumers have the best purchasing power? Where the highest concentrations of consumers? Which country choose as the preferred language in business relations?
Keywords: African Research